The Impact of Economic, Technological and Demographic Factors on Aggregate Births - Venieris, Yiannis P.; Sebold, Frederick D.; Harper, Richard D. (The Review of Economics and Statistics, 1973)
Yiannis P. Venieris, Frederick D. Sebold, Richard D. Harper, The Impact of Economic, Technological and Demographic Factors on Aggregate Births, The Review of Economics and Statistics, Vol. 55, No. 4 (Nov., 1973), pp. 493-497